Semantic Changes Analysis in Terms for Mentioning Adult Women in Newspapers of the 19th, 20th, and 21st Centuries - Yazid Rukmayadi; Puspa Safitrie; Cucum Rohawati (English Department - University of Sultan Ageng Tirtayasa, 2023)
This study aims to investigate semantic changes of these three terms, related to historical dan social factors influencing the change. The data are collected from 12 articles from newspapers published in the 19th, 20th, and 21st centuries. The theories of semantic change of Aitchison (2013) and Kridalaksana (1993) are used to analyze the data. Stemming from the original meaning of each term, it is found that each term possesses concepts of how women are perceived in society. Historical periods and changed social contexts during the period mark the changed meaning. In Colonial Dutch era, perempuan was used to call 'women from the low social class' and nyonya for ‘Dutch and local aristocrat married women’. After the era of Ethical Politics perempuan underwent amelioration into 'women in general' because the word means ‘respectable, skilled person’. After Indonesian independence, nyonya refers to ‘married women in general’. Meanwhile, at the time perempuan underwent pejoration. To replace it, wanita became a formal term that was used widely. The term wanita reflects women’s dependence toward men. Beginning from the 2000s/post-reform period the term nyonya vanished while perempuan underwent amelioration as it began to use widely replacing wanita due to its more positive meaning. Meanwhile, wanita undergoes pejoration because its association to sexual relation. This study would enrich the area of linguistics and feminism and more researches related to it needed.